Regular multi-component exercise increases physical fitness and muscle protein anabolism in frail, obese, older adults - Villareal, Dennis T. (2010)
Aging is associated with a decline in strength, endurance, balance, and mobility. Obesity worsens the age-related impairment in physical function and often leads to frailty. The American College of Sports Medicine recommends a multi-component (strength, endurance, flexibility, and balance) exercise program to maintain physical fitness. However, the effect of such an exercise program on physical fitness in frail, obese older adults is not known. We therefore determined the effect of a 3 month-long multi-component exercise training program, on endurance (peak aerobic capacity [VO(2)peak]), muscle strength, muscle mass and the rate of muscle protein synthesis (basal rate and anabolic response to feeding) in nine 65-80 year-old, moderately frail, obese older adults. After 3 months of training, fat mass decreased (P <0.05) whereas fat-free mass, appendicular lean body mass, strength, and peak aerobic capacity (VO(2) peak increased (all P <0.05). Regular strength and endurance exercise increased the mixed muscle protein fractional synthesis rate (FSR) but had no effect on the feeding-induced increase in muscle protein FSR (~0.02 %/h increase from basal values both before and after exercise training; effect of feeding: P = 0.02; effect of training: P = 0.047; no interaction: P = 0.84). We conclude that: i) a multi-component exercise training program has beneficial effects on muscle mass and physical function and should therefore be recommended to frail, obese older adults, and ii) regular multi-component exercise increases the basal rate of muscle protein synthesis without affecting the magnitude of the muscle protein anabolic response to feeding.